Nurses’s knowledge and attitude in facing potential landslide disasters - Dwi Wahyu Sani S Karenhadi; Indah Dwi Pratiwi; Risa Herlianita; Indri Wahyuningsih (Universitas Muhammadiyah Semarang, 2021)
Landslide is one of the natural disasters which cause not only infrastructure damage but also death. Nurses have a role in disaster management at the phase of mitigation to rehabilitation during landslide disasters. This study is aimed to analyze nurses' knowledge and attitudes in the face of future landslide disasters. A quantitative method with a descriptive design was used in the study. The respondents in this study were 20 nurses who work at one rural community health center in Malang. Data were collected using a questionnaire. From the current research, most respondents had been involved in disaster emergency response activities (85%), had good knowledge (75%), and all nurses (100%) had a positive attitude towards landslide disaster preparedness. From this current study, nurses' knowledge and attitudes towards preparedness for facing landslides might be essential to build more awareness among nurses in preparing the community in facing landslides; thus, the impact of the disaster could be decreased.